Essentially Derived Varieties: Registration under Protection of Plant Varieties and Farmers' Rights Act 2001* - ANURUDH K. SINGH,; ASHOK K. SINGH,; S.K. JAIN, (Seed Research, 2026)
The Protection of Plant Varieties and Farmers' Rights Act, 2001 has provision for registration of "essentially derived varieties" (EDV). By definition EDV is a variety developed from a protected "initial variety" (IV), retaining most essential characteristics of IV and incorporating at least one additional distinguishable characteristic. However, the questions related with genetic similarity between EDV and IV, thereby its dependency on IV for essential characteristics, act of derivation and distinctiveness for additional trait(s) are still being debated for identification criteria/methods and threshold levels to be used for their assessment. In addition, registration of EDV is linked with authorisation from the breeder of IV and benefit sharing on commercialisation. The present article discusses these issues, their implications and the action required to achieve the objectives envisaged in the Act, particularly in relation to breeders' rights, researchers' rights and benefit sharing.